2022
DOI: 10.3390/su14106202
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Mechanisms and ESG Reporting: Evidence from the Saudi Stock Market

Abstract: The code of corporate governance in Saudi Arabia places a greater focus on social responsibility initiatives by Saudi companies and the reporting of such activities to the community. The current study examines the relationship between corporate governance mechanisms and environmental, social, and governance (ESG) disclosures amongst Saudi companies. In particular, we extend previous studies by covering unique Saudi corporate governance mechanisms (i.e., the presence of members of the royal family on the board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 99 publications
7
35
1
Order By: Relevance
“…Moreover, to protect their reputation, royal family members might avoid violations or behavior that could compromise ethical standards while doing business; hence, the authors confirmed a positive relationship between the presence of royal family directors and CSR reporting. Similarly, Bamahros et al (2022) found that the presence of royal family members on board significantly increased the ESG disclosure in Saudi publicly listed firms. Hence, corporate governance was found to be helpful in restricting the unfavorable effects of politically connected board members; it also improves firms’ transparency (Al-Hadi et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, to protect their reputation, royal family members might avoid violations or behavior that could compromise ethical standards while doing business; hence, the authors confirmed a positive relationship between the presence of royal family directors and CSR reporting. Similarly, Bamahros et al (2022) found that the presence of royal family members on board significantly increased the ESG disclosure in Saudi publicly listed firms. Hence, corporate governance was found to be helpful in restricting the unfavorable effects of politically connected board members; it also improves firms’ transparency (Al-Hadi et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 89%
“…Prior literature offers opposing results on the influence of royal family board members on ESG disclosure. While Bamahros et al (2022) showed that royal family members increase ESG disclosure, Al-Bassam et al (2018) reported negative effect of royal family on ESG disclosure.…”
Section: Introductionmentioning
confidence: 94%
“…Ismail and Latiff (2019) submit that board age diversity, board capabilities, and board reputation are significantly and positively influencing ESGD. In a study conducted in Saudi Arabia, it was found that having a royal family on the firm board increases ESGD (Bamahros et al, 2022).…”
Section: Determinants Of Esgdmentioning
confidence: 99%
“…Just like the woman on the board, audit committee gender diversity also positively influences a firm's ESG performance (Bravo & Reguera-Alvarado, 2019). Bamahros et al (2022) found that having external members on the audit committee can enhance ESG activities. Besides the audit committee's characteristics, Hammami and Zadeh (2020) submit that audit quality, as well as public media exposure, can drive higher firms' ESG transparency.…”
Section: Determinants Of Esgdmentioning
confidence: 99%
“…Firm size is an important internal factor affecting ESG disclosure, and most studies have demonstrated a positive relationship between firm size and ESG disclosure (Ali et al 2018;Chen et al 2022a;Gallego-Alvarez and Quina-Custodio 2016;Lu and Abeysekera 2014;Miklosik et al 2021;Mura et al 2019;Nguyen et al 2021). Corporate governance has a strong influence on ESG disclosure (Bae et al 2018;Bamahros et al 2022), and a high level of corporate governance facilitates the legitimate management and disclosure of social responsibility information (Liu and Zhang 2017). Corporate governance promotes CSR reporting in the form of a socially responsible board of directors, while government shareholding influences the quality of CSR reporting, and corporate governance moderates some of the cultural influences that are detrimental to CSR reporting (Adnan et al 2018).…”
Section: Intrinsic Dynamics Of Esg Disclosurementioning
confidence: 99%